ANALISIS KESEJAHTERAAN MIGRAN DI INDONESIA - Nufi Alabshar; Sri Rum Giyarsih; Agus Joko Pitoyo (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2021)
Migration is one of the solutions for survival. Furthermore, migration also provides an opportunity to improve the economy and family welfare. In addition to positive impacts, migration also has negative impacts. These positive and negative impacts make migrant welfare as a result of migration is interesting to study. This study aims to analyze how is the welfare of migrants when viewed through the variable of housing and asset ownership. This study uses secondary data sourced from 2015 Inter-Census Population Survey data (SUPAS 2015). The description of migrant welfare is seen through the housing quality and asset ownership. The results showed that through housing and asset ownership variables, migrants tend to have a good welfare even if compared to non-migrants. This shows the important role of the government in accommodating both the distribution of migration flows and the equitable distribution of resources in Indonesia.